Barriers and facilitators to delivering injury prevention interventions in English children's centres. Issue 2 (3rd March 2016) - Goodenough, Trudy; Kay, Bryony; Deave, Toity; Towner, Elizabeth; Stewart, Jane; Ablewhite, Joanne; Hawkins, Adrian; McDaid, Lisa A; Pitchforth, Emma; Beckett, Kate; Kendrick, Denise
Abstract : The aim of this study is to understand barriers and facilitators to the delivery of injury prevention programmes in English children's centres (CCs). Unintentional injury is a major cause of disability and death in children aged 1–4 years; those living in poverty are at greatest risk. CCs are pivotal in English public health strategies to improve outcomes and reduce inequalities for disadvantaged children through health promotion and family support. This study is part of the National Institute for Health Research funded 'Keeping Children Safe at home' programme, which aims to develop a better understanding of how to prevent unintentional injuries in pre-school children. Thirty-three interviews with CC staff from 16 CCs across four study sites, Nottingham, Norwich, Newcastle and Bristol, explored practitioners' experience of factors that impact on their implementation of health promotion and injury prevention interventions. Using Framework Analysis, managed by NVivo, key facilitators and barriers were identified across all levels of CCs' operation. Facilitators included knowledge of policies and strategies in injury prevention, partnership working and effective parent engagement. Barriers included paucity of national and local injury data, difficulties reaching disengaged families and funding constraints. The challenge is to learn from those who work in CCs the best ways to harness facilitators and to address barriers to child injury prevention activities, and to provide support, including practical advice, for further development of their essential work in injury prevention.